Development of the ENC Android Application for Electronic Nursing Care - Minanton, Minanton; Khoirunnisa, Nurfitria; Habsyah Saparidah Agustina (Information Technology and Science (ITScience), 2025)
The rapid digitalization of the healthcare sector is transforming nursing education and practice, particularly in the area of clinical documentation. In Indonesia, as mandated by Peraturan Menteri Kesehatan Nomor 24 Tahun 2022, all healthcare facilities must document patient medical histories electronically. However, nursing students face challenges in practicing electronic documentation due to limited access to hospital-based EMR systems. This study aims to develop an Electronic Nursing Care (ENC) application as an Android-based platform for nursing students to practice digital documentation aligned with national nursing standards, such as SDKI (Indonesian Nursing Diagnosis Standards), SLKI (Indonesian Nursing Outcomes Standards), and SIKI (Indonesian Nursing Interventions Standards). The ENC application was developed using an Agile methodology, consisting of five sprints: backend development, core features, UI/UX integration, advanced features, and comprehensive internal testing. A 2023 prototype trial demonstrated high user satisfaction, with 93% of students expressing satisfaction with the app’s user interface and experience. The ENC application was designed to reduce the administrative burden on nursing students by offering tools for documenting the nursing process, including assessment, diagnosis, planning, implementation, and evaluation. The initial results indicate that the application meets technical specifications and has the potential to enhance nursing education by providing a structured, user-friendly platform for digital documentation. The study suggests further pilot testing in clinical settings, development of additional features, and ongoing evaluation to ensure the application’s success in nursing education and clinical practice.